Powder material and powder material paste

JP2025025985APending Publication Date: 2025-02-21NIPPON ELECTRIC GLASS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023131293
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、耐酸性に優れ、低温で焼成でき、かつ不活性雰囲気中で焼成しても金属成分が析出し難い粉末材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025985000001
    Figure 2025025985000001
Patent Text Reader

Abstract

To provide a powder material with superior acid resistance, the ability to sinter at low temperatures, and resistance to metal component precipitation even when sintered in an inert atmosphere.SOLUTION: A powder material has a glass composition including, in mol%, 20-60% of ZnO, 10-40% of B2O3, 5-30% of SiO2, 0.1-13% of V2O5, 0-4% of Al2O3, 0-5% of Li2O+Na2O+K2O, 0-5% of MgO, 0-13% of CaO, 0-4% of Bi2O3, and 0-1% of Fe2O3, while being substantially free of PbO.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder material and a powder material paste, for example, to a powder material and a powder material paste for forming an overcoat layer on an electronic circuit or the like. [Background technology]

[0002] The overcoat layer is formed to protect and insulate resistors and the like formed on a substrate such as a soda lime glass substrate or an alumina substrate. Conventionally, a powder material paste has been used to form the overcoat layer. This powder material paste is generally a mixture of glass powder and vehicle, and ceramic powder may be added as necessary.

[0003] The overcoat layer is formed by firing a powder material paste applied onto a substrate on which resistors and the like are formed. The firing temperature is limited to 650°C or less to prevent deterioration of the characteristics of resistors and the like due to a reaction between the resistors and the powder material. For this reason, the powder material (powder material paste) is required to be able to be fired at a temperature of 650°C or less. In addition, the powder material is also required to not warp the substrate after firing, and not to easily peel off from the substrate.

[0004] The electronic circuit on which the overcoat layer is formed may be subjected to a plating process to impart properties such as corrosion resistance, optical properties, mechanical properties, and electrical properties. In this plating process, the overcoat layer is immersed in a plating solution. The plating solution is usually an acidic solution. For this reason, when the plating process is performed, the overcoat layer is required to be acid resistant. In other words, the powder material is required to be acid resistant. In order to adjust the resistance value of the resistor within a certain range, it is necessary to trim the overcoat layer and part of the resistor by irradiating a near-infrared laser (wavelength: 1064 nm) such as Nd:YAG or Nd:YVO4 from above the overcoat layer.

[0005] As a powder material that satisfies the above required characteristics, PbO-B2O3-SiO2 glass has been used up until now (see Patent Document 1).

[0006] In recent years, from the viewpoint of environmental protection, reduction of environmental load substances, for example, reduction of PbO, has been promoted, and various lead-free glasses have been proposed to replace PbO-B2O3-SiO2-based glasses. For example, Patent Documents 2 to 4 describe Bi2O3-B2O3-ZnO-based glasses. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 58-64245 [Patent Document 2] JP 2009-221027 A [Patent Document 3] JP 2007-63105 A [Patent Document 4] Patent No. 4598008 Summary of the Invention [Problem to be solved by the invention]

[0008] Incidentally, when an easily oxidizable material such as Cu is used as a part of the resistor, the powder material paste is fired in an inert atmosphere such as nitrogen, argon, or helium.

[0009] However, when the glasses described in Patent Documents 1 to 4 are fired in an inert atmosphere, metallic lead or metallic bismuth precipitates, making it difficult to maintain properties such as insulation, which is a problem.

[0010] An object of the present invention is to provide a powder material which is excellent in acid resistance, can be sintered at a low temperature, and is less likely to precipitate metal components even when sintered in an inert atmosphere. [Means for solving the problem]

[0011] As a result of various experiments, the present inventors found that the above technical problems can be solved by a ZnO-B2O3-SiO2-V2O5-based glass powder having a specific composition, and propose it as the present invention. That is, the glass powder of the present invention is characterized by containing, in mole percent, 20-60% ZnO, 10-40% B2O3, 5-30% SiO2, 0.1-13% V2O5, 0-4% Al2O3, 0-5% Li2O+Na2O+K2O, 0-5% MgO, 0-13% CaO, 0-4% Bi2O3, and 0-1% Fe2O3, and is substantially free of PbO. Here, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O, and K2O. "Substantially free of" means that the component is not intentionally added as a glass component, and does not mean that even impurities that are inevitably mixed in are completely excluded. Specifically, this means that the content of the relevant component, including impurities, is less than 0.1% by mass.

[0012] The powder material of the present invention preferably has a softening point of not more than 640° C. Here, the “softening point” refers to the value of the fourth inflection point measured by a macro-type differential thermal analyzer (DTA).

[0013] The powder material of the present invention has a linear thermal expansion coefficient of 50×10 -7 / ℃~80×10 -7 / ° C. Here, the "linear thermal expansion coefficient" is a value measured in the temperature range of 30 to 300° C. using a thermomechanical analyzer (TMA).

[0014] The powder material of the present invention is preferably used to form an overcoat layer.

[0015] The powder material paste of the present invention is characterized by containing the above-mentioned powder material and a vehicle. Effect of the Invention

[0016] According to the present invention, it is possible to provide a powder material which has excellent acid resistance, can be sintered at a low temperature, and is less likely to precipitate metal components even when sintered in an inert atmosphere. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The powder material of the present invention is characterized by having a glass composition containing, in mole percent, 20-60% ZnO, 10-40% B2O3, 5-30% SiO2, 0.1-13% V2O5, 0-4% Al2O3, 0-5% Li2O+Na2O+K2O, 0-5% MgO, 0-13% CaO, 0-4% Bi2O3, and 0-1% Fe2O3, and is substantially free of PbO. The reasons for restricting the content range of each component as described above are explained below. In addition, in the explanation of the content range of each component, % means mol%.

[0018] ZnO is a component that lowers the softening point and the linear thermal expansion coefficient. The content of ZnO is 20 to 60%, preferably 35 to 55%, and more preferably 45 to 52%. If the content of ZnO is small, the softening point rises, making it difficult to sinter at a temperature of 650°C or less. In addition, the linear thermal expansion coefficient rises, and the stress caused by the difference in the linear thermal expansion coefficient between the overcoat layer and the resistor increases, making the overcoat layer more likely to crack. On the other hand, if the content of ZnO is large, the acid resistance is more likely to decrease.

[0019] B2O3 is a component that forms a glass skeleton and further expands the vitrification range. The content of B2O3 is 10 to 40%, preferably 15 to 35%, and more preferably 18 to 30%. When the content of B2O3 is low, the thermal stability is likely to decrease. On the other hand, when the content of B2O3 is high, the acid resistance is likely to decrease.

[0020] SiO2 is a component that forms the glass skeleton and also enhances acid resistance. The SiO2 content is 5 to 30%, preferably 7 to 25%, and more preferably 10 to 22%. If the SiO2 content is low, the acid resistance is likely to decrease. On the other hand, if the SiO2 content is high, the softening point rises and it becomes difficult to sinter at a temperature of 650°C or less.

[0021] V2O5 is a component that enhances acid resistance. The content of V2O5 is 0.1 to 13%, preferably 2 to 11%, and more preferably 3 to 9%. If the content of V2O5 is low, the acid resistance is likely to decrease. On the other hand, if the content of V2O5 is high, the thermal stability is likely to decrease.

[0022] Al2O3 is a component that increases the acid resistance, but also significantly increases the softening point. The content of Al2O3 is 0 to 4%, preferably 0.1 to 3%, and more preferably 0.5 to 2%. If the content of Al2O3 is low, the acid resistance is likely to decrease. On the other hand, if the content of Al2O3 is high, the softening point rises, making it difficult to sinter at temperatures below 650°C.

[0023] Li2O, Na2O and K2O are components that lower the softening point, but also components that lower the acid resistance and thermal stability. The total amount and individual content of Li2O, Na2O and K2O is 0 to 5%, preferably 0 to 2%, and more preferably 0 to 1%. If the total amount and individual content of Li2O, Na2O and K2O increases, the acid resistance and thermal stability tend to decrease.

[0024] MgO is a component that lowers the softening point, but also reduces the acid resistance. The content of MgO is 0 to 5%, preferably 0.1 to 4.5%, and more preferably 0.5 to 4%. If the content of MgO is low, the softening point rises, making it difficult to sinter at a temperature of 650°C or less. On the other hand, if the content of MgO is high, the acid resistance is likely to decrease.

[0025] CaO is a component that lowers the softening point and stabilizes glass, but also lowers acid resistance. The CaO content is 0 to 13%, preferably 1 to 12%, and more preferably 3 to 10%. If the CaO content is low, the softening point rises and it becomes difficult to fire at a temperature of 650°C or less. On the other hand, if the CaO content is high, the acid resistance is easily reduced.

[0026] Bi2O3 is a component that lowers the softening point without significantly lowering the acid resistance, but is a component that is easily reduced and precipitates as a metal component during firing in an inert atmosphere. The content of Bi2O3 is 0 to 4%, preferably 0 to 3%, and more preferably 0.1 to 1%. When the content of Bi2O3 is low, the softening point rises and firing at a temperature of 650°C or less becomes difficult. On the other hand, when the content of Bi2O3 is high, metal components are easily precipitated during firing in an inert atmosphere.

[0027] An appropriate amount of Fe2O3 has the effect of increasing the thermal stability of glass, but if the amount is too large, it is a component that decreases the thermal stability. The content of Fe2O3 is 0 to 1%, preferably 0 to 0.8%, and more preferably 0.1 to 0.6%. Whether the content of Fe2O3 is small or large, the thermal stability is easily decreased.

[0028] From an environmental standpoint, it is preferable that the composition contains substantially no PbO, and also contains substantially no F or Cl.

[0029] In the powder material of the present invention, the softening point is preferably 640° C. or less, particularly 635° C. or less. If the softening point is too high, the firing temperature must be increased to obtain a dense overcoat layer, and in that case, the resistor and the powder material react with each other, which tends to deteriorate the characteristics of the resistor and the like. The lower limit of the softening point is not particularly limited, but is practically 500° C. or more.

[0030] In the powder material of the present invention, the linear thermal expansion coefficient is 50×10 -7 / ℃~80×10 -7 / ℃, especially 53×10 -7 / ℃~70×10 -7 / ° C. In this way, the stress caused by the difference in the linear thermal expansion coefficient between the overcoat layer and the resistor is reduced, making it difficult for cracks to occur in the overcoat layer.

[0031] In the powder material of the present invention, the average particle size D 50 is preferably 3 μm or less, and the maximum particle size D maxThe average particle size D is preferably 20 μm or less. 50 , maximum particle size D max If the average particle diameter D is too large, the smoothness of the overcoat layer is likely to deteriorate. 50 " refers to the value measured by a laser diffraction device, and indicates the particle size at which the cumulative amount accumulates to 50% from the smallest particle in the cumulative particle size distribution curve measured by the laser diffraction method. max " refers to a value measured using a laser diffraction device, and indicates the particle size at which the integrated amount accumulatively accounts for 99% of the total volume of particles in the cumulative particle size distribution curve measured using a laser diffraction method, starting from the smallest particle.

[0032] In order to adjust trimming properties, the powder material of the present invention may be used by adding powders such as cordierite, willemite, β-eucryptite, alumina, mullite, zircon, etc. as filler powder. The amount of filler powder added is preferably 0 to 10 parts by mass, 0.1 to 9 parts by mass, and particularly 1 to 8 parts by mass, per 100 parts by mass of the powder material. If the amount of filler powder added is too large, the proportion of the powder material becomes too small relatively, making it difficult to form a dense overcoat layer. From the viewpoint of the smoothness of the overcoat layer, the average particle size D of the filler powder is preferably 0.1 to 9 parts by mass, and particularly preferably 1 to 8 parts by mass. 50 It is preferable that the thickness is 0.2 to 10 μm.

[0033] The powder material paste of the present invention is characterized in that the powder material is the above-mentioned powder material in the powder material paste containing a powder material and a vehicle. Here, the vehicle is a material for dispersing the powder material to make it into a paste, and is usually composed of a resin, a plasticizer, a solvent, etc.

[0034] Next, a method for producing the powder material and the powder material paste of the present invention will be described.

[0035] First, molten glass is formed into a film, and the obtained glass film is then crushed and classified to produce a powder material made of glass (hereinafter, referred to as a glass powder material).

[0036] The glass powder material and the vehicle are then mixed and kneaded in a predetermined ratio to prepare a powder material paste. The vehicle may contain, for example, an organic solvent, a resin, a plasticizer, a dispersant, etc.

[0037] The organic solvent is a material for turning the glass powder material into a paste, and for example, terpineol (Ter), diethylene glycol monobutyl ether (BC), diethylene glycol monobutyl ether acetate (BCA), 2,2,4-trimethyl-1,3-pentadiol monoisobutyrate, dihydroterpineol, etc. can be used alone or in combination. The content is preferably 10 to 40 mass%.

[0038] The resin is a component that increases the strength of the film after drying and imparts flexibility, and its content is generally about 0.1 to 20 mass %. The resin may be a thermoplastic resin, specifically, polybutyl methacrylate, polyvinyl butyral, polymethyl methacrylate, polyethyl methacrylate, ethyl cellulose, etc., which may be used alone or in combination.

[0039] The plasticizer is a component that controls the drying speed and gives flexibility to the dried film, and its content is generally about 0 to 10 mass %. As the plasticizer, butyl benzyl phthalate, dioctyl phthalate, diisooctyl phthalate, dicapryl phthalate, dibutyl phthalate, etc. can be used, and these are used alone or in combination.

[0040] As the dispersant, an ionic or nonionic dispersant can be used, and as the ionic dispersant, a polycarboxylic acid dispersant such as a dicarboxylic acid dispersant, an amine dispersant, etc. can be used, and as the nonionic dispersant, a polyester condensation type dispersant or a polyhydric alcohol ether type dispersant can be used. The amount of the dispersant used is generally 0 to 5% by mass.

[0041] To form an overcoat layer using the powder material paste, first, the powder material paste is applied to a substrate on which a resistor or the like is formed by screen printing, batch coating, or the like to form a coating layer of a predetermined thickness, and then dried to obtain a dry film. The dry film is then fired at a temperature of 550 to 650°C for 5 to 20 minutes to form a predetermined overcoat layer. If the firing temperature is too low or the firing time (retention time) is too short, the dry film is not sintered sufficiently, making it difficult to form a dense fired film. On the other hand, if the firing temperature is too high or the retention time is too long, the resistor or the like reacts with the powder material, and the characteristics of the resistor or the like tend to deteriorate.

[0042] Although the method of forming the overcoat layer has been described using a powder material paste as an example, other methods may be selected, such as a green sheet method, a photosensitive paste method, a photosensitive green sheet method, etc.

[0043] The glass powder material and the powder material paste of the present invention are preferably used to form an overcoat layer of a chip resistor. EXAMPLES

[0044] The present invention will be described in detail below with reference to examples. Note that the present invention is not limited to the following examples. The following examples are merely illustrative.

[0045] Table 1 shows examples of the present invention (samples Nos. 1 to 4) and comparative examples (samples Nos. 5 and 6).

[0046] [Table 1]

[0047] First, the raw materials were prepared and mixed uniformly to obtain the glass composition shown in Table 1. The raw materials were then placed in a platinum crucible and melted at 1200°C for 2 hours. Next, a portion of the molten glass was poured into a stainless steel mold as a sample for measuring the linear thermal expansion coefficient, and the remaining molten glass was formed into a film using a water-cooled roller. The obtained glass film was pulverized in a ball mill and then air-classified to determine the average particle size D 50 3μm or less, maximum particle size D max A glass powder material having a particle size of 20 μm or less was obtained. The softening point of the obtained glass powder material was evaluated.

[0048] The softening point was determined as the value of the fourth inflection point measured by a macro-type differential thermal analyzer (DTA).

[0049] The linear thermal expansion coefficient was measured by measuring the linear thermal expansion coefficient of the above-mentioned measurement sample in the temperature range of 30 to 300° C. using a thermomechanical analyzer (TMA).

[0050] Next, the glass powder material and a vehicle (terpineol containing 5% by mass of ethyl cellulose and 3% by mass of acetyl tributyl citrate) were mixed and kneaded in a three-roll mill to obtain a powder material paste. The powder material paste was then applied by screen printing onto an alumina substrate with a ruthenium oxide (RuO2) resistor to obtain an overcoat layer of approximately 10 μm, after which the applied film was dried and fired in an electric furnace at 640°C for 10 minutes in a nitrogen atmosphere. Using the obtained substrate with the overcoat layer, the presence or absence of precipitation of metal components and the acid resistance were evaluated.

[0051] The presence or absence of precipitation of metal components was evaluated by trimming the above-mentioned substrate with the overcoat layer using an Nd:YAG laser (wavelength: 1064 nm), and then observing the trimmed area with a scanning electron microscope (SEM). Those where no metal components were precipitated were evaluated as "O", and those where metal components were precipitated were evaluated as "X".

[0052] Acid resistance was evaluated as follows: the substrate with the overcoat layer was immersed in 0.05 mol / L sulfuric acid at 30° C. for 30 minutes, washed with water, dried, and then the mass loss was measured and the mass loss ratio (mass loss ratio (%)=(mass of overcoat layer before immersion−mass of overcoat layer after immersion) / (mass of overcoat layer before immersion)×100) was calculated. A mass loss ratio of 0.5% by mass or less indicates excellent acid resistance.

[0053] As is clear from the table, samples Nos. 1 to 4 have a low softening point of 638°C or less and a linear thermal expansion coefficient of 54×10 -7 / ℃~60×10 -7 / °C, which was the desired value. Furthermore, no metal components were precipitated, and the acid resistance was excellent. On the other hand, metallic bismuth was precipitated in sample No. 5. Sample No. 6 was poor in acid resistance. [Industrial Applicability]

[0054] The powder material and powder material paste of the present invention are particularly suitable for forming an overcoat layer, in particular for forming an overcoat layer for a chip resistor, but can also be used for other purposes, such as a binder for electronic component materials and a sealing material.

Claims

1. The glass composition is, in mole percent, ZnO 20 to 60%, B 2 O 3 10-40%, SiO 2 5-30%, V 2 O 5 0.1-13%, Al 2 O 3 0-4%, Li 2 O+Na 2 O+K 2 O 0-5%, MgO 0-5%, CaO 0-13%, Bi 2 O 3 0-4%, Fe 2 O 3 A powder material containing 0-1% PbO and substantially no PbO.

2. 2. The powder material according to claim 1, characterized in that it has a softening point of 640° C. or less.

3. Linear thermal expansion coefficient is 50 x 10 -7 / ℃~80×10 -7 3. The powder material according to claim 1, wherein the temperature is 0.15 to 1.5°C.

4. 3. The powder material according to claim 1, which is used for forming an overcoat layer.

5. A powder material paste comprising the powder material according to claim 1 or 2 and a vehicle.

Citation Information

Patent Citations

  • Glass for covering resistor

    JP1983064245A

  • Nonlead glass composition

    JP2007063105A

  • Lead-free low-melting-point glass composition having acid resistance

    JP2009221027A

  • Acid-resistant lead-free glass composition and glass paste

    JP4598008B2